Mobile Application to Calculate the Parameters of Top Wear Basic Design - Zhylenko, T.I.; Kudryavtsev, A.M.; Zakharkevich, O.V. (Science and Innovation, 2024)
Introduction. Thanks to a rapid advancement of technology, the clothing industry is rapidly developing into a high-tech and capital-intensive production. This contributes to a high quality of design, pattern cutting, and manufacture. The industry is one of the fastest growing in the manufacture sector. Therefore, it is extremely important to enable industry professionals and researchers to keep pace with changes to achieve the desired competitiveness of products. Mobile applications for the garment industry (Stylebook, Cloth, Polyvore, etc.) have been analyzed. These applications contain galleries of clothing models, but only for specific styles of fashion and unrecognizable sizes. Therefore, they can be used as a guide for creating clothes of similar fashion styles but without the necessary level of accuracy. Problem Statement. Mobile applications that are now available for use in the clothing industry are oriented towards the sale of finished products. Since the design and manufacturing stages are provided with software products only at the "home" level, there is a need for the development of mobile applications for clothing industry experts. To develop such an application, it is advisable to choose a design methodology that is both simple, accessible, and known to a wide range of users. Purpose. To develop a mobile application for calculating the parameters of the main blocks of clothing. Materials and Methods. To create our application, an advanced and convenient programming language Kotlin has been used. Results. Based on the comparative analysis of the means of calculating the basic clothing designs, the expediency of using mobile applications in the garment industry has been proved. The existing mobile applications that are used or can be used in the design and manufacture of clothing have been classified. The quantitative classification analysis has confirmed the original hypothesis on the lack of mobile applications used while making a typical basic design. To calculate the parameters of the basic design of top wear, a mobile application has been developed. It provides support for the automated process of creating clothes designs, both in individual or small-scale production, as well as in the learning process. Conclusions. The developed package enables making specific drawings for top wear of any size. The user gets the coordinates of basic design for making patterns for mass production or for individual pattern cutting.